Feasibility of Systematic Respiratory-Gated Acquisition in Unselected Patients Referred for 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography - Robin, Philippe; Bourhis, David; Bernard, Brieuc; Abgral, Ronan; Querellou, Solène; Le Duc-Pennec, Alexandra; Le Roux, Pierre-Yves; Salaün, Pierre-Yves (Frontiers in Medicine, 2018)
Objective Respiratory motion in FDG-PET/CT induces blurred images, leading to errors in location and quantification for lung and abdominal lesions. Various methods have been developed to correct for these artefacts, and most of current PET/CT scanners are equipped with a respiratory gating system. However, they are not routinely performed because their use is time-consuming. The aim of this study is to assess the feasibility and quantitative impact of a systematic respiratory-gated acquisition in unselected patients referred for FDG-PET/CT, without increasing acquisition time. Methods Patients referred for a FDG-PET/CT examination to the nuclear medicine department of Brest University Hospital were consecutively enrolled, during a 3 month-period. Cases presenting lung or liver uptakes were analysed. Two sets of images were reconstructed from data recorded during a unique acquisition with a continuous table speed of 1mm/s of the used Biograph mCT Flow PET/CT scanner: standard free-breathing images, and respiratory-gated images. Lesion location and quantitative parameters were recorded and compared. Results From October 1st 2015 to December 31st 2015, 847 patients were referred for FDG-PET/CT, 741 underwent a respiratory-gated acquisition. Out of them, 213 (29%) had one or more lung or liver uptake but 82 (38%) had no usable respiratory-gated signal. Accordingly, 131 (62%) patients with 183 lung or liver uptakes were analysed. Considering the 183 lesions, 140 and 43 were located in the lungs and the liver respectively. The median (IQR) difference between respiratory-gated images and non-gated images was 18% (-4 − 32) for SUV max, increasing to 30% (14 − 57) in lower lobes for lung lesions, and - 18% (-40 − -4) for MTV (p<0.05). Technologists’ active personal dosimetry and mean total examinations duration were not statistically different between periods with and without respiratory gating. Conclusion This study showed that a systematic respiratory-gated acquisition without increasing acquisition time is feasible in a daily routine and results in a significant impact on PET quantification. However, clinical impact on patient management remains to be determined.